2014
DOI: 10.1111/are.12441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different plant oils on growth performance, fatty acid composition and flesh quality of rainbow trout (Oncorhynchus mykiss)

Abstract: This experiment intended to assess the effect of sesame (SO), sunflower (SFO) and linseed (LO) oils on growth performance, fatty acid composition of fillet and liver or flesh quality traits of rainbow trout. Fish fed different four iso-nitrogenous and iso-lipidic experimental feeds. The control feed contained only fish oil as the primary lipid source. The fillet eicosapentaenoic acid and docosahexaenoic acid levels were the highest in fish fed control feed. In contrast, the liver eicosapentaenoic acid level wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 42 publications
5
24
0
Order By: Relevance
“…; Yildiz et al . ). As extensively reported, certain vegetable oils (VO) are considered good alternatives to FO in diets for salmonids and freshwater fish (Bell et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Yildiz et al . ). As extensively reported, certain vegetable oils (VO) are considered good alternatives to FO in diets for salmonids and freshwater fish (Bell et al .…”
Section: Introductionmentioning
confidence: 97%
“…In view of the increasing global demand of fish oil (FO), its decreasing availability and its large use by the aquaculture industry (FAO, 2014) oils from vegetable origin have been widely studied as sustainable and economically valuable FO substitutes in aqua feeds (Bell et al 2001;Ng et al 2003;Turchini et al 2009;Yildiz et al 2014). As extensively reported, certain vegetable oils (VO) are considered good alternatives to FO in diets for salmonids and freshwater fish (Bell et al 2001;Caballero et al 2002;Fountoulaki et al 2009; Dernekbas ßı 2012).…”
mentioning
confidence: 99%
“…This ingredient is thus progressively replaced by more sustainable alternative lipid sources in fish feed. In this context, plant-derived oils are considered as promising alternatives [ 18 ] and have already been included in commercial feeds without compromising fish growth performance [ 23 26 ]. Nevertheless, plant-derived oils do not contain n-3 LC-PUFA, which decreases the amount of EPA and DHA in the feeds and, consequently, the farmed fish, compromising their nutritional benefits to human consumers [ 18 , 23 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, PO contains a high proportion of palmitic acid (PA, 16:0) with considerable quantities of oleic and linoleic acids (Ng & Gibon, ). Many studies have indicated that FO replacement with VOs did not show any negative effects on growth performance, feed utilization and survival in fish, such as rainbow trout ( Oncorhynchus mykiss ) (Yildiz, Eroldoğan, Engin, Gulçubuk, & Baltaci, ; Yildiz, Kose, Issa, & Kahraman, ) and turbot ( Scophthalmus maximus L .) (Peng et al, ).…”
Section: Introductionmentioning
confidence: 99%